Virus-Based MicroRNA Silencing and Overexpressing in Common Wheat (Triticum aestivum L.) - Jian, Chao (Front Plant Sci, 2017)
MicroRNAs (miRNAs) are a class of endogenous small non-coding RNAs that arise from large RNA precursors with a stem-loop structure and play important roles in plant development and responses to environmental stress. Although a hundred and nineteen wheat miRNAs have been identified and registered in the miRBase (Release 21.0, June, 2014; http://www.mirbase.org), the functional characterization of these miRNAs in wheat growth and development is lagging due to lack of effective techniques to investigate endogenous miRNA functions in wheat. Here we report barley stripe mosaic virus(BSMV)-based miRNA overexpression and silence systems that can be applied to study miRNA functions in wheat. By utilizing the BSMV system, we successfully knocked down endogenous miR156 and miR166 levels and over-expressed endogenous miR156 and artificial miRNA against phytoene desaturase gene PDS (amiR-PDS) in wheat. amiR-PDS expression caused a great reduction in endogenous mRNA abundance of PDS gene in wheat plant, leading to leaf obviously photobleaching. miR156 silencing led to a great increase in the mRNA level of its target gene SPL2, resulting in a leaf-curl phenotype in wheat seedlings. In contrast, overexpression of miR156 led to a significant reduction in the mRNA level of SPL2 in wheat seedlings, resulting in serious delay of the vegetative phase transitions as well as booting and flowering in wheat. These confirmed that miR156 regulates wheat development and booting time through SPL genes. In summary, the BSMV-based miRNA overexpression and silence systems have extraordinary potential not only for functional study of protein-encoding genes but also for miRNA genes in wheat.